Application of Plan-DO-Check-Action cycle in materials management of outpatient clinics during the COVID-19 outbreak (PDCA循环在新型冠状病毒肺炎疫情防控期间门诊疫情防控物资管理中的应用) - WANG Ting (王婷); PENG Aiqin (彭爱琴); LIU Nan (刘楠); LI Jia (李佳); GAO Lini (高黎妮) (中西医结合护理)
Objective To investigate the Plan-DO-Check-Action (PDCA) cycle in materials management of outpatient clinics during the COVID-19 outbreak. Methods The PDCA cycle method was adopted in materials management of outpatient clinics during the COVID-19 outbreak, a management procedure consisting of planning, implementation, checking, effectiveness measurement and continuous improvement was carried out to improve the efficiency of materials usage. The material expenditure before implementation of PDCA cycle (January 2020) and after implementation of PDCA cycle (May 2020) was analyzed. Results The usage efficiency of materials for prevention of control of COVID-19 was improved after implementation of PDCA cycle. Conclusion The PDCA cycle is an effective tool of improving the quality and efficiency of materials management in outpatient clinics during the COVID-19 outbreak (目的 探讨PDCA 循环在新型冠状病毒肺炎疫情防控期间门诊疫情防控物资管理中的应用效果。方法 运用PDCA循环制定新型冠状病毒肺炎疫情防控期间门诊疫情防控物资管理的措施, 通过计划、实际执行、检查、效果确认及持续改进等, 提高疫情防控物资管理和使用效率。对比分析PDCA实施之前(2020年1月)和PDCA 实施后(2020年5月)门诊疫情防控物资支出情况。结果 实施PDCA循环后, 门诊疫情防控物资使用管理效率较实施前明显提高。结论 PDCA循环可以提升门诊疫情防控物资管理效率。)